Microhematuria assessment an IBCN consensus-Based upon a critical review of current guidelines - Schmitz-Draeger, Bernd J.; Kuckuck, Eva C.; Zuiverloon, Tahlita C. M.; Zwarthoff, Ellen C.; Saltzman, Amanda; Srivastava, Abhishek; Hudson, M'Liss A.; Seiler, Roland; Todenhoefer, Tilmann; Vlahou, Antonia; Grossman, H. Barton; Schoenberg, Mark P.; et al. (Urologic Oncology-Seminars and Original Investigations, 2016)
Assessment of patients with asymptomatic microhematuria (aMh) has been a challenge to urologists for decades. The aMh is a condition with a high prevalence in the general population and also an established diagnostic indicator of bladder cancer. Acknowledging aMh needs to be assessed within a complex context, multiple guidelines have been developed to identify individuals at high risk of being diagnosed with bladder cancer.This structured review and consensus of the International Bladder Cancer Network (IBCN) identified and examined 9 major guidelines. These recommendations are partly based on findings from a long-term study on the effects of home dipstick testing, but also on the assumption that early detection of malignancy might be beneficial.Despite similar designs, these guidelines differ in a variety of parameters including definition of aMh, rating of risks, use of imaging modalities, and the role of urine cytology. In addition, recommendations for further follow-up after negative initial assessment are controversial. In this review, different aspects for aMh assessment are analyzed based upon the evidence currently available.We question whether adherence to the complicated algorithms as recommended by most guidelines is practical for routine use. Based upon a consensus, the authors postulate a need for better tools. New concepts for risk assessment permitting improved risk stratification and prepone cystoscopy before refined imaging procedures (computed tomography scan and magnetic resonance imaging) are suggested.
EVALuna2:16348